Gatekeeping Perspektif Westley dan Mclean pada Berita Bola www.pikiran-rakyat.com - Gumiliar, Fajar; Hermawandi, Yandi; ., Firmansyah (CV. ITTC INDONESIA, 2025)
This study addresses the challenge faced by digital media in maintaining accuracy and preventing the spread of hoaxes, particularly in football journalism. The rapid flow of digital content requires media organizations to maintain public trust without compromising journalistic standards. In this context, the information filtering process becomes crucial to ensure the credibility and quality of news content presented to the audience. The aim of this study is to explore the application of Bruce Westley and Malcolm McLean’s gatekeeping theory in the production of football news at www.pikiran-rakyat.com. The research focuses on the roles of the communicator (reporter) and the gatekeeper (editor) in determining which information is fit for publication. This research uses a qualitative method to gain an in-depth understanding of newsroom practices. Data were collected through unstructured interviews and documentation of journalistic work routines. The data analysis follows Miles and Huberman’s interactive model, consisting of three core components: data reduction, data display, and conclusion drawing and verification. The findings reveal that reporters and editors collaborate in performing the gatekeeping function. Reporters are responsible for identifying relevant news issues and producing accurate, neutral narratives, while editors filter and refine content to align with editorial standards. The study concludes that Westley and McLean’s model is effective in describing editorial mechanisms in preventing misinformation and maintaining news quality within the competitive digital media landscape.